(untitled) (ModaPalavra e-periódico, 2011)
To establish what are the criteria for making professional uniforms requires much more than the choice of aesthetic codes. It is necessary to develop innovative approaches and techniques. One of the main information says regarding the analysis of the work environment, since each profession is held in a particular physical space and thus there are risks inherent in that space. When trying to understand the interconnections of environmental risks and design of clothing, it is clear that we need a prior knowledge of the process of making uniform as materials, modeling and notions in general. This integration is key to the expansion of thought, reflection, and finally to the execution of a professional uniform as a protective equipment. This study demonstrates concisely a tool for identify the environmental hazards present in a work environment.